Metagenomic analysis reveals gut phage diversity across three mammalian models - Menghao Yu; Yunmeng Chu; Yongming Wang; Luofei Mo; Xin Tan; Shun Guo; Shengjian Yuan; Yingfei Ma (Microbiome)
Abstract Background The gut virome plays a pivotal role in shaping the host’s microbiota. However, gut viruses across different mammalian models, and their connections with the human gut microbiota remain largely unknown. Results We identified 977 high-confidence species-level viral operational taxonomic units (vOTUs) in mice (hcMGV), 12,896 in pigs (hcPGV), and 1480 in cynomolgus macaques (hcCMGV) from metagenomes, respectively. Clustering these vOTUs at approximately genus level uncovered novel clades with high prevalence across animal guts (> = 60%). In particular, crAss-like phages and cas-harboring jumbophages were characterized. Comparative analysis revealed that hcCMGV had a closer relationship with hcPGV than hcMGV, despite the animal-specific characteristics, and that 55.88% hcCMGV had connections with the human microbiota. Conclusions Our findings shed light on the diversity of gut viruses across these three animals, contributing to future gut microbial studies using model animals. Video Abstract